SIMULATION OF THE WETTING PATTERN UNDER SURFACE DRIP IRRIGATION AND GRAVEL GROOVE - Ahmed Shihab Ahmed (Diyala Journal of Engineering Sciences, 2016)
A groove filled with gravel under the soil surface is presented in this research to study the influence of groove’s dimensions and emitter’s discharge on the wetting pattern directions in the heavy soil under surface drip irrigation systems. Dimensional analysis techniques were used for predicting the wetting pattern directions functions and the comparison with the experimental work was carried out. The laboratory tests were conducted in a clay loam soil steel container using groove filled with gravel under the soil surface of width 10 cm and 20 cm and at emitter’s discharge 1.3 l/hr and 2 l/hr. The results showed that the groove’s width has effected on dimensions of the wetting patterns front. The increasing of the groove’s width caused increase in the soil water movement in downward and horizontal directions by an average value of 19.1% and 8.9%, respectively. Also, the increasing of the groove’s width had an inverse effect on the water upward direction; the average value dropped by 19.9%. Moreover, increasing value of the emitter’s discharge influenced on the increasing and decreasing of the upward, horizontal and downward water directions. Increasing of the emitter’s discharge, saturation state was taken place inside the groove due to the clay particles in the soil. The statistical analysis for the comparison among the predicted wetting patterns equations developed by the dimensional analysis techniques with the experimental measured data showed a good agreement. The RMSE and R2 were varied from 1.18 cm to 1.847 cm and from 0.98 to 0.99, respectively.